2022
DOI: 10.1039/d2en00785a
|View full text |Cite
|
Sign up to set email alerts
|

Few-layer graphitic carbon nitride for enhanced visible-light photocatalytic efficiency: the role of narrow bandgap and nitrogen-vacancies

Abstract: Graphitic carbon nitride (g-C3N4) was a famous photocatalyst with vast perspectives in the field of visible-light photocatalysis, while the actual performance was inhibited by the feeble efficiencies in charge-carriers separation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The transient photocurrent responses of Fe 2 O 3 –Au@SiO 2 exhibited the highest photocurrent signals, which was indicative of the highest separation efficiency of charge carriers. 42 The EIS Nyquist plots showed that Fe 2 O 3 –Au@SiO 2 had the smallest impedance arc radius among the three catalysts (Fig. 3c), suggesting weaker interfacial charge transport resistance and faster migration of electrons.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The transient photocurrent responses of Fe 2 O 3 –Au@SiO 2 exhibited the highest photocurrent signals, which was indicative of the highest separation efficiency of charge carriers. 42 The EIS Nyquist plots showed that Fe 2 O 3 –Au@SiO 2 had the smallest impedance arc radius among the three catalysts (Fig. 3c), suggesting weaker interfacial charge transport resistance and faster migration of electrons.…”
Section: Resultsmentioning
confidence: 96%
“…40 In the XPS spectrum of O, the main peak of the O 1s orbital was divided into three peaks, whose electron binding energy was located at 530.0 eV, 531.8 eV and 532.9 eV, representing lattice O, OH and absorbed H 2 O, respectively. 41 To explore the photovoltaic properties in the light-harvesting process and the charge separation and transfer efficiency, PL 42 The EIS Nyquist plots showed that Fe 2 O 3 -Au@SiO 2 had the smallest impedance arc radius among the three catalysts (Fig. 3c), suggesting weaker interfacial charge transport resistance and faster migration of electrons.…”
Section: The Physicochemical Characteristics Of Fementioning
confidence: 99%
“…These properties allow it to be a promising confined template to directly grow 2D nanosheets. 41 Typically, 1.0 g CoCl 2 ·6H 2 O with 1.0 g template RUB-15 was mechanically ground uniformly, calcined at 500 °C at a rate of 2 °C min −1 in a tube furnace, and then was kept under 500 °C for 360 min. The calcination atmosphere was varied according to actual demand, as A-Co 3 O 4 /SiO 2 , hemi-Co 3 O 4 /SiO 2 , and C-Co 3 O 4 /SiO 2 were obtained with pure Ar, gas mixture (Ar : air = 1 : 2) and pure air, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in our comprehensive analysis of charge separation dynamics, the concurrent decrease in both PL and TRPL intensities serve as an indicative measure of diminished recombination and improved charge separation. The existence of midgap states in N‐vacancy CN synthesized through diverse methods including thermal condensation utilizing a covered ceramic arc, [133] acetamide‐ or formamide‐assisted in situ approaches, [99] a three‐step thermal exfoliation method, [62] polycondensation using RUB‐15 template, [168] and Molten salt‐assisted method [169] has been verified. Additionally, the impact of these midgap states on the photocatalytic activity of CN was carefully investigated.…”
Section: Unlocking N‐vacancies In Cn: Characterization Techniquesmentioning
confidence: 99%